The Religiosity's Impact on Social Piety and English Learning Motivation Among Muslim High School Students in Salatiga and Semarang - Mashlihatul Umami; Ruwandi Ruwandi (Sekolah Tinggi Agama Islam Al-Furqan, Makassar - Indonesia, 2024)
This study is conducted to analyze the influence of religiosity on social piety and the significance level of the influence between the two, to analyze the effect of religiosity on English learning motivation along with the significance between the two and analyze the relationship between religiosity with social piety and English learning motivation and the significance of the relationship. The data sampling technique used in this study is random sampling. The data collection techniques that will be used to collect research data are questionnaire and documentation. The results of this study found that there is an insignificant positive correlation between religiosity and motivation to learn English because the t score (1.664) is smaller than the t table score (2.664). The same is also shown by the significance value because the significance value (0.102) is greater than 0.05; and a significant correlation between social diversion and English learning motivation because to (X2) is greater than tt (2.738 > 2.394). The same is shown by the significance value because the significance value score (0.008) is smaller than 0.05. The contribution of religiosity and social diversion to learning motivation is 22% (rounding), while the remaining 78% is influenced by other variables outside the model. Furthermore, the adjusted R² coefficient which is the correlation of R² is 0.192. This means that the correlation does not yet describe its closeness to the population. Then, together there is a positive and significant correlation between religiosity and social diversion with motivation to learn English because F count is greater than F table with df 57 and a significance level of 5%. The calculated F score is 8.015 while the F table is 4.010. With the comparison between the score of F count with F table which shows that Fo > Ft, it can be concluded that the independent variables together have a significant effect on the dependent variable.